Loss of Frrs1l disrupts synaptic AMPA receptor function, and results in neurodevelopmental, motor, cognitive and electrographical abnormalities - Michelle Stewart; Petrina Lau; Gareth Banks; Rasneer Sonia Bains; Enrico Castroflorio; Peter L. Oliver; Christine L. Dixon; Michael C. Kruer; Dimitri M. Kullmann; Abraham Acevedo-Arozena; Sara E. Wells; Silvia Corrochano; et al. (The Company of Biologists, 2019)
Loss-of-function mutations in a human AMPA receptor-associated protein, ferric chelate reductase 1-like (FRRS1L), are associated with a devastating neurological condition incorporating choreoathetosis, cognitive deficits and epileptic encephalopathies. Furthermore, evidence from overexpression and ex vivo studies has implicated FRRS1L in AMPA receptor biogenesis, suggesting that changes in glutamatergic signalling might underlie the disorder. Here, we investigated the neurological and neurobehavioural correlates of the disorder using a mouse Frrs1l null mutant. The study revealed several neurological defects that mirrored those seen in human patients. We established that mice lacking Frrs1l suffered from a broad spectrum of early-onset motor deficits with no progressive, age-related deterioration. Moreover, Frrs1l−/− mice were hyperactive, irrespective of test environment, exhibited working memory deficits and displayed significant sleep fragmentation. Longitudinal electroencephalographic (EEG) recordings also revealed abnormal EEG results in Frrs1l−/− mice. Parallel investigations into disease aetiology identified a specific deficiency in AMPA receptor levels in the brain of Frrs1l−/− mice, while the general levels of several other synaptic components remained unchanged, with no obvious alterations in the number of synapses. Furthermore, we established that Frrsl1 deletion results in an increased proportion of immature AMPA receptors, indicated by incomplete glycosylation of GLUA2 (also known as GRIA2) and GLUA4 (also known as GRIA4) AMPA receptor proteins. This incomplete maturation leads to cytoplasmic retention and a reduction of those specific AMPA receptor levels in the postsynaptic membrane. Overall, this study determines, for the first time in vivo, how loss of FRRS1L function can affect glutamatergic signalling, and provides mechanistic insight into the development and progression of a human hyperkinetic disorder. This article has an associated First Person interview with the first author of the paper.